2015
DOI: 10.1093/neuonc/nou349
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy versus partial versus gross total resection in older patients with high-grade glioma: a systematic review and meta-analysis

Abstract: Our findings suggest an upward improvement in survival time, functional recovery, and tumor recurrence rate associated with increasing extents of safe resection. These benefits did not result in higher rates of mortality or morbidity if considered in conjunction with known established safety measures when managing elderly patients harboring HGGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 80 publications
10
104
1
Order By: Relevance
“…The currently available data suggest that surgical resection may play an important role [32, 33]. Adjuvant therapy is still a subject of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The currently available data suggest that surgical resection may play an important role [32, 33]. Adjuvant therapy is still a subject of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several prognostic factors for better outcomes in glioma patients have been reported, which include age, genetic mutations, achievement of gross total resection (GTR)3456. Among these factors, achievement of GTR was found to be crucial for the better prognosis78910. Incomplete resection, even in low grade gliomas, leads to higher probability of recurrence and shorter survival by residual tumor1112.…”
mentioning
confidence: 99%
“…Further studies suggest similar survival advantage in patients who underwent complete resection vs. partial resection providing level 2b evidence of the benefit of surgery in high-grade glioma. A recent meta-analysis included an analysis of 12,607 patients from 34 studies and concluded that there is an improvement in survival times, functional recovery and tumour recurrence rate with increasing extents of safe resection [33]. However, there is an important but inherent bias in all studies that suggest Improved survival in primary and secondary malignant astrocytoma Nomiya et al [21] Retrospective, single centre 170 patients with anaplastic astrocytoma EOR was the most important prognostic factor on multivariate analysis Stummer et al [22] Phase III RCT, multi-centre 322 patients with suspected malignant glioma 5-ALA enables a more complete resection which leads to improved progression-free survival Keles et al [23] Retrospective, single centre 102 adult patients with hemispheric anaplastic astrocytoma Volume of residual disease was the most important prognostic indicator on time to tumour progression Pope et al [24] Retrospective, single centre 110 patients with glioblastoma, 41 patients with anaplastic astrocytoma EOR was not a statistically meaningful predictor of survival Ushio et al [25] Retrospective, single centre 105 consecutive patients with hemispheric glioblastoma Progression-free survival and overall survival was significantly better in the gross total resection group compared to the partial resection group and biopsy group Puduvalli et al [26] Retrospective, multi-centre 106 patients with anaplastic oligodendroglioma 'A trend towards longer survival with a greater extent of resection' a survival advantage; patients who undergo total resection are usually younger, with a good performance status and have a glioma in a non-eloquent location.…”
Section: The Value Of Extent Of Resectionmentioning
confidence: 99%